'Let them have it!' A review of the retention and storage of, and access to, material post conviction in England and Wales. (October 2019) - Shorter, Louise; Madland, Geir
Records kept, physical material seized, samples taken and extracts derived during a criminal investigation are retained post conviction in case they could assist a subsequent appeal against conviction. Forensic evidence is the application of scientific analysis to the law. Its presentation in court involves not just the material itself but a suitably learned scientist's opinion of its significance, and that opinion may be called into question, scientific understanding being in constant flux. Scientific opinion presented in court today may be superseded tomorrow – a powerful argument for the retention of all material which could be subjected to new tests or interpretation in the light of new information. But are exhibits being retained appropriately? A Freedom of Information request to all police forces in England and Wales was undertaken to ascertain their retention practices. The far-from-uniform results are presented and discussed here, along with policy recommendations.